(untitled) (Social Science Review, 2023)
In Bangladesh, various forms of violence are much higher in the remote areas of the southern coastal districts than in any other part of the country. Though there are a number of legal support-related organisations available in the country, they have limited presence in the coastal areas. Hence, based on ten in-depth interviews, this paper focuses on women’s personal reflections on their experience of domestic violence and their attitude towards seeking help to protest against violence. The research findings reveal that although domestic violence takes place inside the family, however, is strengthened by the broader patriarchal structure and legitimised through the practice of negative socio-cultural discourses, religious beliefs, norms, and gender bias legal systems. The findings further establish that patriarchal mentality, traditional norms and discourses, women’s insecurity, lack of education and economic dependency of women create hindrance from receiving legal assistance, which in turn create further scope for domestic violence. Social Science Review, Vol. 39(3), Dec 2022 Page 37-54